The Correlation between Dye absorption Wavelength and Illumination Wavelength on DSSC Performance - Hery Suyanto; Manuntun Manurung; I Putu Tedy Indrayana; Fiar Tri Santika (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
This study examines the effect of the wavelength of light illuminated on DSSC on the absorption wavelength and gap dye energy. The dye used was sea lettuce anthocyanin from Sanur Beach, Bali. As much as 20 grams of dried sea lettuce powder was dissolved in 80 mL of 96% ethanol and 6% HCl. After 24 hours of immersion, it was filtered with Whatman 41 paper. The filtrate was characterized using a UV-Vis-NIR spectrophotometer so that the absorption wavelengths of the anthocyanin dye were 272.5 nm, 417 nm, and 653.5 nm. The gap energy was calculated using the Tauc Plot method, and the result was 2.826 eV. The dye was applied to make DSSC using the sandwich method, which was then irradiated with white, red, and purple LEDs with respective wavelengths of 400–700 nm (with peaks at 439.67 nm and 550.29 nm), 629.04 nm and 425.38 nm and variations in intensity values, namely 1000 lux, 2000 lux, and 3000 lux. Illumination using purple LEDs produces the maximum current and highest efficiency compared to white and red, namely 1.33 mA, 1.57 mA, and 1.83 mA for 1000 lux, 2000 lux, and 3000 lux, respectively, and the efficiency is 0.0039 for 1000 lux. The purple color has a wavelength close to and intersects with the absorbance wavelength of the dye and has energy (2.918 eV) greater than the gap energy of the sea lettuce dye.